Gluten-free baked muffins developed with Prosopis alba flour - Sciammaro, Leonardo Pablo (2018)
Baked flour products are basic in people´s diet; the problem arises when celiac people tend to follow this kind of diet. In this work we exploit the benefit of American carob, Prosopis alba flour (PAF) in developing gluten-free muffins jointly with corn flour (CF) and rice flour (RF). All muffins obtained presented very good physical and sensory characteristics. The muffin with the highest amount of PAF presented low chewiness and was the most adhesive. Crumb structure of muffins with PAF presented alveoli of more irregular form although they occupied a greater proportion of area, leading to softer crumbs. Sample with high content of PAF presented the greatest score for sensory overall acceptability and the lowest for chewiness; also the intensive brown color was also well accepted by consumers. Nutritional analysis of the muffins indicate that those products with the highest content of PAF (66.6%) presented higher amount of proteins, ash and dietary fiber and lower of lipids. Also, these muffins presented a high amount of polyphenols and the highest antioxidant activity. Sensory and nutritional analysis showed that PAF contributed in a positive form to muffin´s quality, suggesting that this flour would be a suitable ingredient as mimetic of chocolate-based breads.